Asprothrips bimaculatus sp.n. (Thripidae, Dendrothripinae) from Martinique - Michel, Bruno; Ryckewaert, Philippe (Zootaxa, 2014)
Asprothrips bimaculatus sp. n. is described from Martinique. It is unique among the five species now recognised in this genus in having the body sharply bicoloured, with the head and thorax dark but the abdomen white.